Evaluation of Arginase and Nitric oxide levels in Sepsis - R Mulgund, Shruti; A Abhang, Subodhini (International Journal of Medical Research and Review, 2014)
Introduction: Sepsis is one of the challenges for the doctors who treat critically ill patients. Delay in diagnosis and late administration of antibiotics have been shown to increase mortality in this cohort. In the present study CRP is used as a traditional marker of an acute inflammatory state and infection. In last couple of years use of Arginase as immune marker has increased enormously. An interplay between Arginase and Nitric oxide has also been reported in immune cells including macrophages, lymphocytes etc. due to limited availability of Arginine in sepsis. Keeping all these facts in mind, present study was designed. Aims and Objectives: To find out the diagnostic role of Arginase and Nitric oxide in sepsis and to compare with CRP level. Material & Methods: Thirty patients admitted in MICU of Sassoon Hospital, Pune having SIRS and thirty age, sex matched healthy controls were included in this study. Intravenous blood samples were obtained and analyzed. CRP was done by kit method, Arginase activity was estimated by Roman and Ray method while NO levels were measured by Cortas & Wakid method. Results and Conclusion: The results of this study showed significant increase in the levels of CRP. Serum arginase was also increased significantly with concomitant decrease in the levels of nitric oxide when compared with healthy controls. So we can conclude from the results that nitric oxide and arginase levels along with CRP may be useful in diagnosis of sepsis.